Pyrene core-based red and near-infrared luminescent materials with thermally activated delayed fluorescence properties for luminescent layer doping materials
By designing red light and near-infrared TADF material based on pyrodiazine receptors, combined with double (3,5-two-unedicinel benzhenyl) amines amines amine, soluble to electronic groups, solved the existing TADF material OLED device Preparation to rely on vacuum steam plating method has realized the preparation of high -efficiency and low -cost solution processing, and expanded the research of near -infrared launchers.
Patent Information
- Application Number
- CN202411489970.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The preparation of OLED devices with existing red light and near-infrared TADF materials mainly relies on vacuum evaporation method, resulting in waste of raw materials, high costs, complex processes, and insufficient development of solution processing methods.
A class of red light and near-infrared light-emitting materials based on pyrodiazine receptors are designed. By introducing double (3,5-two-unedicinel phenyl) amine as an increased solubility to the electronic group, it has a delay in thermal activation delay. Fluorescent materials are suitable for the preparation of solution processing.
Realize the preparation of high -efficiency, low -cost red light, near -infrared OLED devices, reduce waste of raw materials, improve the feasibility and efficiency of craftsmanship, and expand related research on near -infrared launchers.
Smart Images

Figure CN119371428A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic electroluminescent materials, and specifically discloses a type of red and near-infrared luminescent materials with thermally activated delayed fluorescence characteristics based on pyrene cores and used as luminescent layer doping materials. Background Art
[0002] As one of the most important applications of near-infrared luminescent materials, near-infrared OLEDs not only play an important role in night vision equipment, optical communications, and information security display fields, but are also used in flat panel displays and lighting equipment. Many types of emitters are used in NIR OLEDs, such as metal complexes, conjugated polymers, phosphorescent metal complexes, etc. These materials give NIR OLEDs excellent properties, such as light weight, low power consumption, fast response time, good processing performance, wide temperature range, and low cost.
[0003] The first generation of traditional fluorescent materials can only use singlet excitons to emit light, and their internal quantum efficiency is 25%, resulting in the maximum theoretical external quantum efficiency (EQE) of fluorescent OLEDs devices being only 5%, which is not commercially available and limits the further development of this type of material. In order to seek a breakthrough, in 1998 Forrest G.
[0004] The development of organic electroluminescent materials based on metal complex porphyrin platinum has brought the second generation of organic electroluminescent materials - phosphorescent materials - to the stage. Since this type of material can make full use of singlet and triplet excitons to emit light, it can achieve a theoretical internal quantum efficiency of 100%, greatly improving the luminous efficiency of the material.
[0005] Compared with fluorescent materials, phosphorescent materials show lower driving voltage and high efficiency. In the display field, their vividness, color saturation, high contrast and other advantages make them commercialized. However, their cost and stability problems are significant, so the third generation of organic light-emitting materials - thermally activated delayed fluorescence (TADF) materials were born. In 2009, Adachi's team first demonstrated the application of thermally activated delayed fluorescence materials in OLEDs, which brought great changes to the development of OLEDs. This type of material does not contain heavy metals and can obtain 100% internal quantum efficiency (IQE). It is known as the third generation of organic light-emitting materials. It has lower cost, better environmental protection, and is more conducive to the industrialization development of OLEDs. It has become an important research direction for organic electroluminescent materials.
[0006] Professor Wang Yue et al. reported the first NIR TADF molecule TPA-DCPP in 2015. The pyrazine derivative 2,3-dicyanopyrazinephenanthrene (DCPP) with an extended conjugated structure was selected as the electron withdrawer. The effective HOMO-LUMO separation and partial orbital overlap generated by the D-π-A-π-D configuration ensured that the ΔE of TPA-DCPPST As small as 0.13eV and 9.0×10 -7 s -1 Big K f It shows broad near-infrared emission with a maximum wavelength of 708nm, and the Φ PL The value is 14%. However, the non-doped OLED device based on TPA-DCPP was prepared by vacuum evaporation, showing a maximum EQE of 2.1% and an EL peak at 710nm.
[0007] Liao and his colleagues developed a new TADF material, in which a new acceptor dibenzo[a,c]phenazine-3,6-dicarbonitrile (PZCN) was used. The large and planar structure of the material is conducive to suppressing non-radiative transitions. In 2021, they designed and synthesized a series of efficient red / DR TADF materials. By introducing strong electron-withdrawing groups from pyridyl (PY) to trifluoromethyl (CF3) and cyano (CN), the emission wavelength in the DR region was rationally regulated. The internal conversion (IC) process of these materials was greatly suppressed by the incorporation of molten polycyclic aromatic hydrocarbons (dibenzo[a,c]phenazine). However, due to the introduction of rigid conjugated groups, the solubility of the material is greatly reduced, and the device preparation requires vacuum evaporation.
[0008] From the above research, it can be found that most OLED devices made of TADF materials are currently prepared by vacuum evaporation. In particular, the solubility of long-wavelength materials (red-near infrared materials) decreases significantly due to the increase in their conjugation degree. This method often leads to waste of raw materials, high costs, and complex processes in mass production. The preparation of devices based on solution processing still needs further development. Summary of the invention
[0009] In order to expand the molecular structure design of red light and near-infrared TADF materials that are efficient and can be processed in solution. The present invention uses pyrene with excellent physical and chemical properties as the molecular structure center, designs two pyrene-pyrazine derivative receptors (symmetrical and asymmetrical), and then uses bis(3,5-di-tert-butylphenyl)amine as a solubilizing electron-donating group to synthesize a class of red light and near-infrared luminescent materials based on pyrene-pyrazine receptors with thermally activated delayed fluorescence characteristics that can be processed in solution. This type of material has the following structure:
[0010]
[0011] The preferred structure of this type of material is shown below:
[0012]
[0013] By modifying the structure of the pyrene core, two pyrene-pyrazine derivative acceptor groups (symmetrical and asymmetrical) were constructed, and bis(3,5-di-tert-butylphenyl)amine was used as a solubilizing electron-donating group. The asymmetric acceptor core can provide stronger electron-withdrawing ability, and at the same time can provide some inert groups to increase the solubility of the molecule and inhibit the planar stacking of the rigid part of the acceptor; based on the symmetric acceptor core, it has better solubility, but its electron-withdrawing ability is relatively weak. Two TADF molecules were designed with these two acceptor cores, and the relationship between their photophysics and structure and their applications were studied.
[0014] Another object of the present invention is to provide a red and near-infrared luminescent material of a symmetric acceptor core and an asymmetric acceptor as an organic electroluminescent diode luminescent layer doping material, so as to obtain a red solution-processed organic electroluminescent device with excellent luminescent performance.
[0015] Among them, the main material of the light-emitting layer of the electroluminescent device is TCTA.
[0016] The mass ratio of the luminescent material doped in the luminescent layer is 1-3%.
[0017] The technical advantages of this patent are:
[0018] 1. Utilize the pyrene core's easy modification and excellent physical and chemical properties, such as excellent thermal stability, high fluorescence quantum yield, and easy formation of electroexciton complexes, to construct a series of new red and near-infrared luminescent materials with asymmetric and symmetric receptor cores;
[0019] 2. Using pyrenepyrazine derivatives (symmetrical and asymmetrical) as strong electron acceptors and bis(3,5-di-tert-butylphenyl)amine as electron donors, the two are subjected to bromination, Buchwald–Hartwig coupling and other reactions. Their structures are more conducive to the distortion of the molecular donor and acceptor, and then to the effective separation of the frontier orbitals, that is, the separation of the highest occupied orbital (HOMO) and the lowest occupied orbital (LUMO), which is conducive to reducing ΔE ST , it is easy to obtain TADF characteristics, further improving the luminescence efficiency of the material, while the molecular charge transfer process is enhanced, which is more conducive to achieving red shift of emission;
[0020] 3. The effects of the electron-withdrawing ability and the structure of the acceptor central core on the performance of the entire molecule were systematically studied, which is of great significance for the construction of new red and near-infrared luminescent materials based on the pyrene core.
[0021] The advantages of the present invention are:
[0022] On the one hand: due to the large torsion angle between the donor and the acceptor, the overall planarity of the molecule decreases, which is conducive to inhibiting molecular stacking and thus reducing the quenching of excitons; on the other hand: the modification of the peripheral tert-butyl group makes the molecule have excellent solubility (in chlorobenzene, under heating conditions, the solubility can reach more than 10 mg / mL), and OLED devices can be prepared by solution processing, and the high-efficiency preparation of long-wavelength 650nm solution-processed OLED devices has been achieved. The relevant research on near-infrared emitters has been expanded. The influence of the acceptor cores with different electron-withdrawing ability and structure on the performance of the entire molecule is of great significance for the construction of new red and near-infrared luminescent materials based on pyrene cores. BRIEF DESCRIPTION OF THE DRAWINGS
[0023]
Figure 1
[0024]
Figure 2
[0025]
Figure 3
[0026]
Figure 4
[0027]
Figure 5
[0028] [Figure 6] is a hydrogen nuclear magnetic resonance spectrum of the intermediate of the compound PBCN-4tBuDPA and PB-4tBuDPA prepared in Example 1 of the present invention ( 1 1H NMR) (af).
[0029] [Figure 7] is the H NMR spectra of the compounds PB-4tBuDPA (a) and PBCN-4tBuDPA PB-4tBuDPA (b) prepared in Example 1 of the present invention ( 1 1H NMR). DETAILED DESCRIPTION
[0030] The following specific implementation cases are intended to further illustrate the present invention, but these specific implementation cases do not limit the protection scope of the present invention in any way.
[0031] Example 1
[0032] The synthesis scheme of the red and near-infrared luminescent materials based on the present invention is as follows:
[0033]
[0034] Synthesis of compound M1:
[0035] At room temperature, add (2.0g, 9.6mmol) of pyrene, ruthenium trichloride (246mg, 1.15mmol), 40mL of acetonitrile (CH3CN), 40mL of dichloromethane (CH2Cl2), 50mL of H2O and magnetite to a 500mL two-necked flask, and add (16.9g, 79mmol) of sodium periodate (NaIO4) in three batches. The dark brown reaction solution was reacted at 35°C for 12h. After the reaction was completed, the reaction mixture was washed with 200mL of H2O and the insoluble organic matter was removed by filtration. The filtrate was extracted three times with CH2Cl2 (3×100mL), washed three times with water (3×100mL), dried with anhydrous magnesium sulfate, and filtered to obtain a dark orange solution. The solvent was removed by reduced pressure distillation to obtain a dark orange solid. Column chromatography was performed using pure CH2Cl2 as the eluent to obtain 550 mg of the pure product orange solid M1 (pyrene-4,5,9,10-tetraone) with a yield of 21%. 1 H NMR (400MHz, CDCl3) δ (ppm) 8.52 (d, J = 7.6 Hz, 4H), 7.73 (t, J = 7.6 Hz, 2H).
[0036] Synthesis of compound M2:
[0037] Take a clean and dry 100mL two-necked flask, add 2.0g of pyrene-4,5,9,10-tetraketone (M1) (7.6mmol) and 20mL concentrated H2SO4, place the device in a constant temperature magnetic stirrer, and add (3.4g, 19.0mmol) of N-bromosuccinimide (NBS) three times within 15 minutes at room temperature, then heat to 60℃ and react overnight. After the reaction is completed, cool to room temperature, slowly add dropwise to ice water, stir for 30min, filter, rinse the filter cake with boiling water, and obtain a yellow filter cake, which is then recrystallized with CH2Cl2 and methanol (CH3OH) to obtain 2.8g of yellow powder M2 (2,7-dibromo-pyrene-4,5,9,10-tetraketone), with a yield of 90%. 1 H NMR (400MHz, DMSO) δ (ppm) 8.36 (s, 4H).
[0038] Synthesis of compound M3:
[0039] 1.0g M2 (2,7-dibromo-pyrene-4,5,9,10-tetraketone) (1.0g, 2.3mmol) and p-toluenesulfonic acid monohydrate (546.0mg, 2.8mmol) were added to a 250mL three-necked flask, and ethylene glycol (37.0g, 0.6mol) was dissolved in anhydrous toluene. The device was placed in a constant temperature magnetic stirrer, and a water separator was built (to separate the water produced during the reaction). Under N2 protection, the reaction was carried out at 140°C for 48h. After the reaction was completed, it was cooled to room temperature, and a large amount of methanol was added until a solid precipitated. The filter cake was filtered and dried to obtain 960.0mg of light yellow powder M3 with a yield of 70%. 1 H NMR (400MHz, CDCl3) δ7.85 (s, 4H), 4.17 (s, 8H), 3.62 (s, 8H).
[0040] Synthesis of compound M4:
[0041] Take a clean and dry 250mL single-necked flask and add 4-tert-butylphenylboronic acid (1.0g, 5.6mmol), 4,5-dibromo-o-phenylenediamine (750mg, 1.75mmol), Pd(PPh3)4 (170.0mg, 0.15mmol) and K2CO3 aqueous solution (2mol / L, 7.5mmol) and 60mL of 1,4-Dioxane. Place the device in a constant temperature magnetic stirrer and react at 110℃ under nitrogen protection for 24h. After the reaction is completed, cool to room temperature, remove the organic solvent 1,4-Dioxane by vacuum distillation, and extract with CH2Cl2. Combine the organic phases, add anhydrous magnesium sulfate to dry, use pure CH2Cl2 as eluent, separate by column chromatography to obtain a gray solid, and recrystallize with CH2Cl2 and CH3OH to obtain 490.0mg of white powder product M6 with a yield of 70%. 1 H NMR (400MHz, CDCl3) δ (ppm) 7.17 (d, J = 8.3 Hz, 4H), 7.01 (d, J = 8.3 Hz, 4H), 6.78 (s, 2H), 3.46 (s, 4H), 1.28 (s, 18H).
[0042] Synthesis of compound M5:
[0043] In a 100 mL two-necked bottle, 1-bromo-3,5-tert-butylbenzene (1.5 g, 5.57 mmol) and 3,5-di-tert-butylaniline (1.5 g, 7.24 mmol), tridibenzylideneacetone dipalladium (Pd2(dba)3 (306.0 mg, 0.33 mmol), tri-tert-butylphosphine tetrafluoroborate (TBPBF4) (191.0 mg, 0.66 mmol), sodium tert-butoxide (1.6 g, 16.71 mmol) were added, dissolved in 50 mL of anhydrous toluene, and extracted. The device was placed in a constant temperature magnetic stirrer and stirred at 110°C under argon protection for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, the organic solvent was removed by vacuum distillation, and the mixture was extracted with CH2Cl2. The organic phases were combined, dried with anhydrous magnesium sulfate, and the organic solvent was removed by vacuum rotary distillation. PE and CH2Cl2 were used as eluents (volume ratio = 6:1), and column chromatography was performed to obtain a white solid, which was further recrystallized with CH2Cl2 and CH3OH to obtain 1.65 g of white powder M5 with a yield of 68%. 1 H NMR (400MHz, CDCl3) δ6.97 (s, 6H), 5.74 (s, 1H), 1.31 (s, 36H).
[0044] Synthesis of compound M6:
[0045] In a 100 mL two-necked flask, M3 (807.0 mg, 1.35 mmol), M5 (1.3 g, 3.36 mmol), trisdibenzylideneacetone dipalladium (Pd2(dba)3) (74.0 mg, 0.081 mmol), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (X-Phos) (77.0 mg, 0.162 mmol), potassium tert-butoxide (608.0 mg, 5.4 mmol) were added, dissolved in 50 mL of anhydrous toluene, evacuated, and the apparatus was placed in a constant temperature magnetic stirrer, and stirred at 115 ° C under argon protection for 12 h. After the reaction was completed, the mixture was cooled to room temperature, and the organic solvent was removed by vacuum distillation. The mixture was extracted with CH2Cl2, and the organic phases were combined and dried with anhydrous magnesium sulfate. The organic solvent was removed by vacuum rotary distillation, and column chromatography was performed using PE and CH2Cl2 as eluents (volume ratio = 2:1) to obtain a green solid. The solid was further recrystallized with CH2Cl2 and CH3OH to obtain 1.12 g of purple-black powder M6 with a yield of 68%. 1 H NMR (400MHz, CD2Cl2) δ7.23(s,4H),7.04(s,4H),6.87(s,8H),3.93(s,8H),3.57(s,8H),1.16(s,72H).
[0046] Synthesis of compound M7:
[0047] Compound M6 (1.0 g, 0.8 mmol) and 100 mL trifluoroacetic acid (TFA) were added to a 250 mL three-necked flask and vacuumed. The device was placed in a constant temperature magnetic stirrer and stirred at room temperature for 36 h under argon protection. After the reaction was completed, it was cooled to room temperature, 200 ml of ice water was added, and a black solid was precipitated. The black solid was filtered, the filter cake was rinsed with CH2Cl2, the filtrate was collected, and the organic solvent was removed by vacuum rotary evaporation. PE and CH2Cl2 were used as eluents (volume ratio = 1:1), and column chromatography was performed to obtain a blue-black solid, which was further recrystallized with CH2Cl2 and CH3OH to obtain 780.0 mg of blue-black powder M7 with a yield of 93%. 1 H NMR (400MHz, CDCl3) δ8.06 (s, 4H), 7.18 (s, 4H), 6.92 (s, 8H), 1.25 (s, 72H).
[0048] Synthesis of compounds PBCN-4tBuDPA and PB-4tBuDPA:
[0049] Compound M7 (200.0 mg, 0.19 mmol), M4 (78.0 mg, 2.1 mmol), 60 mL CHCl3 and 15 mL acetic acid were added to a 250 mL three-necked flask, wherein M4 was dissolved in CHCl3, and the mixture was gradually added dropwise through a constant pressure dropping funnel within 3 h. The mixture was evacuated and placed in a constant temperature magnetic stirrer. The mixture was stirred at 85 °C under argon protection for 8 h. Samples were taken to detect whether M7 had reacted completely. After the reaction was complete, an excess of diaminomaleonitrile was added and the reaction was continued for 15 h. After the reaction was completed, the mixture was cooled to room temperature, and the organic solvent was removed by vacuum distillation. The mixture was extracted with CH2Cl2, and the organic phases were combined and dried with anhydrous magnesium sulfate. The organic solvent was removed by vacuum rotary evaporation, and PE and CH2Cl2 were used as eluents (volume ratio = 3:1). Column chromatography was performed to obtain a red solid and a purple-red solid, which were further recrystallized with CH2Cl2 and CH3OH to obtain 70.0 mg of purple-black powder PBCN-4tBuDPA with a yield of 40%; in addition, 80.0 mg of red powder PB-4tBuDPA was obtained with a yield of 24.5%. PBCN-4tBuDPA:1H NMR (400MHz, CDCl3) δ9.64 (s, 2H), 9.16 (s, 2H), 8.20 (s, 2H), 7.29 (d, J = 8.1Hz, 4H ),7.20(s,12H),7.14(d,J=8.0Hz,4H),1.33(s,18H),1.30(s,72H).PB-4tBuDPA: 1 H NMR (400MHz, CDCl3) δ8.21 (s, 4H), 7.32–7.25 (m, 20H), 7.15 (d, J = 8.0Hz, 12H), 1.33 (s, 36H), 1.29 (s, 72H).
[0050] Example 2
[0051] The compounds PBCN-4tBuDPA and PB-4tBuDPA in Example 1 were dissolved in chlorobenzene and heated to 85° C., and their solubilities were 10 mg / mL and 16 mg / mL, respectively.
[0052] The compounds PBCN-4tBuDPA and PB-4tBuDPA in Example 1 were dissolved in toluene to prepare 10 -5 M solution, and tested its UV-visible absorption (UV) and photoluminescence spectrum (PL). Figure 1It can be seen that the UV-visible absorption spectrum of the compound PB-4tBuDPA in solution has roughly two absorption peaks of different intensities: the strong absorption peak at short wavelength (300-406nm) is mainly attributed to the π-π* transition absorption of the molecule; the weak absorption peak at long wavelength (502nm) is attributed to the charge transfer (ICT) transition absorption peak from the electron-donating unit to the electron-withdrawing unit in the molecule. Figure 1 As shown, the maximum emission peak of the compound PB-4tBuDPA is 645nm, which is in the red light region. Figure 2 It can be seen that the UV-visible absorption spectrum of the compound PBCN-4tBuDPA in solution has roughly two absorption peaks: the absorption peak at short wavelength (280-354nm, 413nm) is mainly attributed to the π-π* transition absorption of the molecule; the absorption peak at long wavelength (521nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit in the molecule. Figure 2 As shown, the maximum emission peak of the compound PBCN-4tBuDPA is 745nm, which is in the near-infrared region.
[0053] Example 3
[0054] The fluorescence lifetime of the compound PB-4tBuDPA in Example 1 in a 1 wt % doped TCTA film was tested under vacuum. Figure 3 As shown, the fitting results show that the delayed lifetime of PB-4tBuDPA is 7.3μs, and the delayed component accounts for 78.8%.
[0055] Example 4
[0056] The application of the compounds PB-4tBuDPA and PBCN-4tBuDPA in Example 1 in organic electroluminescent devices. The compound is used as a dopant in the light-emitting layer of the device, and the device structure is an organic electroluminescent diode of ITO / PEDOT:PSS (35nm) / PVK (60nm) / EML (35nm) / DPEPO (6nm) / TmPyPB (55nm) / LiF (0.5nm) / Al (100nm). Among them, PEDOT:PSS is a hole injection layer; PVK is a hole transport layer; DPEPO is a hole blocking layer; TmPyPB is an electron transport layer; LiF / Al is a cathode. EML is a light-emitting layer, including TCTA (light-emitting layer main material) and PB-4tBuDPA or PBCN-4tBuDPA (light-emitting layer dopant), and the doping concentration of the dopant in the light-emitting layer is 1, 2, or 3 wt%. Figure 4As shown in (a), PB-4tBuDPA is used as a dopant, and the electroluminescence spectra of the doping ratio device are 652nm, 652nm, and 654nm, respectively, all in the deep red region. The maximum external quantum efficiency of the device doped with 1, 2, and 3 wt% PB-4tBuDPA is 11.1%, 15.2%, and 9.8%, respectively. Figure 4 (b) shown; wherein the molecular structure of the compound TCTA is as follows Figure 4 (c) As shown. However, the compound PBCN-4tBuDPA showed poor performance, with the EL peak at 706nm and the maximum EQE less than 1%. Figure 5 shown.
[0057] Device solution processing preparation method: The substrate is pretreated with oxygen plasma to increase the function of the ITO film. Then, PEDOT:PSS is spin-coated on the ITO substrate at a speed of 3200rpm for 30 seconds and annealed at 150℃ for 15 minutes to obtain a 35nm thick hole injection layer; PVK is prepared to 10mg / mL and then spin-coated on the hole injection layer as a hole transport layer; the prepared host-guest mixed solution (the doping amount of the luminescent layer dopant is 1, 2, 3wt%, and the solvent is chlorobenzene) is spin-coated on the hole transport layer at 80℃, then annealed for 30 minutes, and then DPEPO, TmPyPB, and LiF / Al cathode are successively evaporated on the luminescent layer, the hole blocking layer, and the electron transport layer to obtain a device containing the luminescent molecule of the present invention.
[0058] Example 5
[0059] The H NMR spectra of the key intermediates M1-3 and M5-7 of the compounds PBCN-4tBuDPA and PB-4tBuDPA in Example 1 are shown in Figures 6(af), respectively.
[0060] Example 6
[0061] The hydrogen nuclear magnetic resonance spectra of the compounds PB-4tBuDPA (a) and PBCN-4tBuDPA (b) in Example 1 are shown in FIG7 .
[0062] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.
Claims
1. A type of red and near-infrared luminescent material based on pyrene core with thermally activated delayed fluorescence characteristics, characterized in that: The molecular structure of the luminescent material is shown below:
2. The red and near-infrared luminescent material with thermally activated delayed fluorescence characteristics based on pyrene core according to claim 1, characterized in that: The molecular structure of the luminescent material is shown below:
3. An application of the red and near-infrared luminescent material with thermally activated delayed fluorescence characteristics based on pyrene core as claimed in claim 1, characterized in that: The red and near-infrared light-emitting materials having thermally activated delayed fluorescence characteristics are used as light-emitting layer doping materials of organic light-emitting diodes.
4. The use of the red and near-infrared luminescent material having thermally activated delayed fluorescence characteristics based on pyrene core as claimed in claim 3, characterized in that: The main material of the light-emitting layer is TCTA.
5. The use of the red and near-infrared luminescent material having thermally activated delayed fluorescence characteristics based on pyrene core as claimed in claim 3, characterized in that: The red and near-infrared luminescent materials with thermally activated delayed fluorescence characteristics are doped in the luminescent layer in a mass ratio of 1-3%.
6. The use of the red and near-infrared luminescent material having thermally activated delayed fluorescence characteristics based on pyrene core as claimed in claim 3, characterized in that: The organic light emitting diode is prepared by a solution processing method.
Citation Information
Patent Citations
Red thermal activation delayed fluorescence material, organic electroluminescent device and preparation method of red thermal activation delayed fluorescence material
CN114292264A
Organic thermal delay fluorescent material based on di-tert-butyl aniline donor and preparation method of organic thermal delay fluorescent material
CN116283984A
Dicyano1H-benzo [d] anthracene-1-one thermally activated delayed fluorescent near-infrared luminescent material and application thereof
CN118561720A